Consumption of Diet Soda Sweetened with Sucralose and Acesulfame‐Potassium Alters Inflammatory Transcriptome Pathways in Females with Overweight and Obesity. Issue 11 (5th May 2020) - Sylvetsky, Allison C.; Sen, Sabyasachi; Merkel, Patrick; Dore, Fiona; Stern, David B.; Henry, Curtis J.; Cai, Hongyi; Walter, Peter J.; Crandall, Keith A.; Rother, Kristina I.; Hubal, Monica J.
Abstract : Scope: Low‐calorie sweetener (LCS) consumption is associated with metabolic disease in observational studies. However, physiologic mechanisms underlying LCS‐induced metabolic impairments in humans are unclear. This study is aimed at identifying molecular pathways in adipose impacted by LCSs. Methods and results: Seven females with overweight or obesity, who did not report LCS use, consumed 12 ounces of diet soda containing sucralose and acesulfame‐potassium (Ace‐K) three times daily for 8 weeks. A subcutaneous adipose biopsy from the left abdomen and a fasting blood sample were collected at baseline and post‐intervention. Global gene expression were assessed using RNA‐sequencing followed by functional pathway analysis. No differences in circulating metabolic or inflammatory biomarkers were observed. However, ANOVA detected 828 differentially expressed annotated genes after diet soda consumption ( p < 0.05), including transcripts for inflammatory cytokines. Fifty‐eight of 140 canonical pathways represented in pathway analyses regulated inflammation, and several key upstream regulators of inflammation (e.g., TNF‐alpha) were also represented. Conclusion: Consumption of diet soda with sucralose and Ace‐K alters inflammatory transcriptomic pathways (e.g., NF‐κB signaling) in subcutaneous adipose tissue but does not significantly alter circulating biomarkers. Findings highlight the need to examine molecular and metabolic effects of LCS exposure in a larger randomized control trial for a longer duration. Abstract : To identify molecular pathways in adipose tissue impacted by low‐calorie sweeteners (LCSs), seven females with overweight/obesity, who did not use LCSs, consumed 12 oz of diet soda containing sucralose and acesulfame‐potassium (Ace‐K) three times daily for 8 weeks. Consumption of diet soda altered genes and molecular pathways involved in inflammation in adipose, but did not alter inflammatory markers in the bloodstream.